Targeting lipid metabolism reprogramming of immunocytes in response to the tumor microenvironment stressor: A potential approach for tumor therapy - Zhang, Ming; Wei, Tingju; Zhang, Xiaodan; Guo, Danfeng (Frontiers in Immunology, 2022)
The concept of the tumor microenvironment (TME) has been proposed over past years, and it has become a research hotspot since then. Distinct from the normal extracellular environment, the alternation in TME has been well identified including nutrient supply, pH value, oxygen content, metabolite abundance, etc. and such changes may promote genesis, proliferation, invasion, and metastasis of carcinoma even the malfunction of immunocytes infiltrating around neoplasm. Due to the deficiency of nutrients and relative components neoplasm demand, tumor cells tend to transform their metabolism pattern by reprogramming glucose, lipid, and amino acid metabolism to adjust to the environmental stressors. Accompanying the in-depth research of carcinoma metabolism reprogramming, growing clues suggest not only tumor cells but immunocytes swift their metabolism routine which is named “immunometabolism” and relative study has arisen increasing attention in academia. In this review, we focus on the recent study progress of lipid metabolism reprogramming in immunocytes within TME and summarize potential targeting molecules, pathways as well as genes. In addition, we shed light on hypoxia, one of the vital altered components of TME that partially contributes to the emergency of abnormal lipid metabolism in immune cells. In the last part, we introduce the current immunotherapies and their targets by mediating the lipid metabolism of immunocytes to potent antitumor immune response. Collectively, we highlight lipid metabolism reprogramming of various immunocytes in TME and provide a novel insight for researchers to consider a promising therapeutic method for tumor therapy.